CREATIVITY OF TARAS HRYHOROVYCH SHEVCHENKO THROUGH THE PRISM OF PSYCHOANALYSIS - Плахотна, С. (Modern engineering and innovative technologies, 2024)
The article provides a psychological understanding of T.H. Shevchenko's creativity from the standpoint of psychoanalysis. Specific features of the psychology of the poet`s creativity are the influence of childhood on creativity, the relationship of though